2022
DOI: 10.3390/ma15113771
|View full text |Cite
|
Sign up to set email alerts
|

Damage Mechanisms and Anisotropy of an AA7010-T7452 Open-Die Forged Alloy: Fatigue Crack Propagation

Abstract: The process–microstructure–property relationship of high-strength 7000 series aluminum alloys during fatigue crack propagation (FCP) is highly relevant for safety during the design and service of aircraft structural components. It is scientifically evident that many metallurgical factors affect FCP properties, but partly contradictory or inconclusive results show that the quantitative description of the relationships is still a major challenge among researchers and engineers. Most research focuses on sheet or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…The second issue is the crystallographic texture. It has been shown experimentally in aluminum alloys that the crystallographic texture has a significant effect on fatigue propagation and total fatigue life [ 25 , 26 ]. Virtual experiments based on numerical simulations also showed that the effect of the texture on fatigue crack initiation is not negligible [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The second issue is the crystallographic texture. It has been shown experimentally in aluminum alloys that the crystallographic texture has a significant effect on fatigue propagation and total fatigue life [ 25 , 26 ]. Virtual experiments based on numerical simulations also showed that the effect of the texture on fatigue crack initiation is not negligible [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, it should be noted that both mechanisms, dynamic precipitation and dislocation multiplication, are simultaneously responsible for the obtained higher flow stress of the as-quenched condition. In the case of the TSM condition, the measured hardening rate θ in the later stages of deformation is higher, as is the noticeably increased particle size and, therefore, the large dislocation mean free path reduces the dislocation particle interactions significantly [39,45]. This phenomenon is explained by the fact that strain hardening is proportional to the ratio of the volume fraction to the size of particles or to the interparticle spacing.…”
Section: Discussionmentioning
confidence: 96%
“…Continuum damage mechanics [ 19 ] has been used to characterize fatigue crack initiation and propagation in general. It provides a macroscopic field variable that reflects the average microstructural material damage [ 20 , 21 ]. This so-called “damage variable” appears in the constitutive relations that regulate a material’s deformation behavior [ 22 ].…”
Section: Introductionmentioning
confidence: 99%